1998
DOI: 10.2214/ajr.171.3.9725285
|View full text |Cite
|
Sign up to set email alerts
|

Doppler waveforms of the normal and collateralized inferior mesenteric artery.

Abstract: OBJECTIVE. Our purposewas to analyzeDoppler waveformchangesand the caliberof the inferior mesenteric artery as a collateral vessel in occlusive disease of the abdominal aorta or its main branches.SUBJECTS AND METHODS. Thirty-threepatients wereexaminedin threegroupsaccord ing to the location of their occlusive disease (group 1 [n = 5], occlusion of the celiac and superior mesenteric arteries;group 2 [n = 9], occlusion ofthe iliac artery;and group 3 [n = 19], occlusion of the abdominal aorta distal to the renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 3 publications
1
22
0
4
Order By: Relevance
“…Ultrasound (US) is cheap, easily applicable and non-invasive, yet operator-dependent [88] and prone to magnification effect and diameter overestimation [20,65,77]. Not all arteries are visualised due to their anatomic position, including CA, SMA and IMA [25,59]. Computerised topographic angiography and magnetic resonance angiography are precise, objective and repeatable [66,99] but method they apply (3-dimensional reconstruction of vessels filled with contrast material) is probably superior for lumen rather than diameter estimation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound (US) is cheap, easily applicable and non-invasive, yet operator-dependent [88] and prone to magnification effect and diameter overestimation [20,65,77]. Not all arteries are visualised due to their anatomic position, including CA, SMA and IMA [25,59]. Computerised topographic angiography and magnetic resonance angiography are precise, objective and repeatable [66,99] but method they apply (3-dimensional reconstruction of vessels filled with contrast material) is probably superior for lumen rather than diameter estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Stent grafts design and placement for endovascular repair of AA and branches aneurysms [38,40], chemoembolisation for haemorrhage or chemotherapy [5], visceral aneurysm diagnosis and treatment [8] and transplantation [36,87] are based on precise calculation of AA branches' diameters. Diagnosis, staging and treatment of many relative common diseases including chronic mesenteric ischaemia or other occlusive diseases of AA branches [25] and chronic renal insufficiency [3] utilise such measurements. Certain morphometric characteristics including volume and length are useful for diagnosis and staging of spleen and kidney diseases like splenomegaly and various nephropathies [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Although PSV of the normal IMA has been shown to range from 93 to 189 cm/second, specific velocities for detecting significant IMA stenosis have never been established. 5 Few authorities proposed certain PSV values, but without supporting data.…”
Section: Discussionmentioning
confidence: 99%
“…Erden et al 5 showed that PSVs in the IMA can reach 190 cm/second when the IMA serves as part of a collateral pathway in the presence of severely stenotic or occluded SMA or CA. Recently, Pellerito et al 9 reported that a PSV >200 cm/second is useful for detecting significant IMA stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation